2019
DOI: 10.1038/s41393-019-0243-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with expressed and unmet service needs reported by persons with spinal cord injury living in the community

Abstract: Study design Observational study. Objectives To determine the prevalence, predictors, and consequences of self-reported service needs among communitydwelling persons with SCI. Setting Community-based, Switzerland. Methods Participants were 490 people who took part in the health services module of the Swiss Spinal Cord Injury Cohort Study (SwiSCI) 2012 community survey. We determined the prevalence of 20 service needs and the extent to which they were unmet. Predictors and consequences of service needs were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
16
1
2
Order By: Relevance
“…Female respondents reported higher needs in all domains and barriers to enjoying life compared with male respondents. This is contrary to the findings of Trezzini et al (2019), where expressed needs were not associated with gender in individuals with SCI despite female participants in their study reporting higher unmet needs for recreation and peer support. Our findings could be a reflection of the demands and expectations placed on women in our environment.…”
Section: Discussioncontrasting
confidence: 99%
“…Female respondents reported higher needs in all domains and barriers to enjoying life compared with male respondents. This is contrary to the findings of Trezzini et al (2019), where expressed needs were not associated with gender in individuals with SCI despite female participants in their study reporting higher unmet needs for recreation and peer support. Our findings could be a reflection of the demands and expectations placed on women in our environment.…”
Section: Discussioncontrasting
confidence: 99%
“…Linking caregivers to resources would help them find the appropriate support when it was most needed. In this regard, the introduction of case management programs could also help; in a recent study in Switzerland nearly half of the respondents reported that their need for case management was at best partially fulfilled [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This nding is surprising, as it was previously reported that individuals with incomplete lesions expressed dissatisfaction with the quality of primary care services in terms of the ful lment of SCI-speci c care needs [11]. However, differences in the need for SCI-speci c care and for a broader range of services between persons with incomplete and complete lesions might explain their choice of rst contact [38]. An additional aspect may be the local availability of specialized care and the travel distance to SCI centres.…”
Section: Interpretation and Comparison With Existing Literaturementioning
confidence: 92%